Families as a Cornerstone in 21st Century Public Health: Recommendations for Research, Education, Policy, and Practice - Weiss-Laxer, Nomi S.; Crandall, AliceAnn; Hughes, Mary Elizabeth; Riley, Anne W. (Frontiers in Public Health, 2020)
Families are vastly overlooked in US initiatives to promote population health and health equity despite being the most proximal context for health across the life course. We urge the public health sector to take the lead in recognizing families as essential for promoting 21st century population health. We highlight ways families influence health by providing context, care, continuity, and connections. The dual private and public aspect of families has contributed to how they have been overlooked in the public health sector. We provide recommendations for better integrating families into population health initiatives through national health goals, research, education, policy, and practice.